2019
DOI: 10.1111/hsc.12764
|View full text |Cite
|
Sign up to set email alerts
|

Women's views of continuity of information provided during and after pregnancy: A qualitative interview study

Abstract: Straightforward transfer of care from pregnancy to the postpartum period is associated with health benefits and is desired by women worldwide. Underpinning this transfer of care is the sharing of information between healthcare professionals and the provision of consistent information to women. In this qualitative study, two aspects of continuity of information were examined; first the information passed on from midwife to health visitor regarding a woman and her baby before the health visitor meets the woman p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
(57 reference statements)
0
5
0
4
Order By: Relevance
“…The concepts of management continuity, informational continuity and relational continuity [32] were useful in describing continuity of care in the postnatal period. Care in terms of the three types of continuity in postnatal care has shown that parents want to have access to care based on their own needs [33,34,40]. There is evidence that continuity of care starting in the prenatal period has a great impact on mothers' mental and physical health, especially when the three types of continuity were highlighted together [34].…”
Section: Discussionmentioning
confidence: 99%
“…The concepts of management continuity, informational continuity and relational continuity [32] were useful in describing continuity of care in the postnatal period. Care in terms of the three types of continuity in postnatal care has shown that parents want to have access to care based on their own needs [33,34,40]. There is evidence that continuity of care starting in the prenatal period has a great impact on mothers' mental and physical health, especially when the three types of continuity were highlighted together [34].…”
Section: Discussionmentioning
confidence: 99%
“…The need for a systematic, universal and effective approach for following up women with GDM has long been recognised [16]. GDM recall registers would be relatively straightforward to set up in primary care, and have been shown to be successful in other countries [17,18] but ensuring that health visitors are aware of women who would benefit from opportunistic advice around T2D risk is more problematic. There appears to be no national consistent approach to handover information from midwife to health visitor, each Health Board having local arrangements in place and midwives sharing information with the health visitor they feel appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Vários autores realçam a má qualidade da informação transmitida como podendo ser geradora de mal estar, ansiedade, baixa autoestima e depressão (Henshaw et al, 2018;Olander et al, 2019;Zhang, et al, 2021) Percebemos que a maternidade é um período peculiar da vida da mulher em que ela se encontra ávida por aprender e se interessa por tudo quanto diga respeito à mãe e à criança, como evidenciado por Olander et al (2019), sendo importante, como referem Slomian et al (2017), as mães receberem informação de qualidade.…”
Section: Discussão/conclusãounclassified
“…A qualidade dos cuidados está asociada à qualidade da informação e da comunicação enfermeiro cliente, sendo importante a forma como a informação é percebida (Amoah et al, 2019), pois os aspetos ligados à mãe e à criança são alvo de grande preocupação por parte das mães (Olander, Aquino, Chhoa, Harris, Lee & Bryar, 2019) A informação transmitida durante a gravidez pelos profissionais de saúde diminui as queixas e aumenta a qualidade de vida das grávidas pelo que se deve ter em consideração não apenas as queixas e preocupações da grávida como a qualidade da informação que lhe é transmitida (Yikar & Nazik, 2019). A educação pré-natal é um dos fatores de proteção para a depressão pré-natal, revelando a importancia da mesma (Zhang, Wang, Cui, Yuan, Huang, & Zhou, 2021), sendo que as mães que apresentam síntomas depressivos no período pós-parto também revelam a necessidade de informação de qualidade (Slomian et al, 2017) Num período tão importante na vida da mulher e da sua familia a atenção dos enfermeiros para com as clientes tem que ser redobrada para evitar que as mães se sintam ignoradas, pela escassa partilha de informação ou pela sua inconsistência (Olander et al, 2019), ou por outro lado se sintam baralhadas e com baixa autoestima pela enorme quantidade de informação ou informação pouco sistematizada e até contraditória (Henshaw et al, 2018) Conhecer a qualidade da informação transmitida pelos profissionais às suas clientes, é uma necessidade, de modo a dirigir o cuidado em função das especificidades de cada mulher e sua familia (Rasteiro, Santos, & Coutinho, 2021) por forma a a experiencia da maternidade possa ser vivida na sua plenitude.…”
Section: Introductionunclassified